Обґрунтування моделі для дослідження параметрів охорони основних похилих виробок у розвантажених від гірського тиску зонах - Янжула, О.С.; Головін, М.В.; Підгурна, О.Ю.; Назимко, В.В.; Захарова, Л.М.; Кусень, О.Б. (Физико-технические проблемы горного производства, 2021)
Мета. Оцінка перерозподілу гірського тиску навколо робочого пласта.
Meтоди. Під час виконання проекту планувальних гірничих робіт використовували дані шахтних інструментальних спостережень зрушень навколо підготовчих виробок за допомогою контурних та глибинних реперів, моніторингу динаміки зростання тиску обвалених порід та підробленої товщі на підошву відпрацьованого вугільного пласта й кінцевих різниць.
Результати. Обґрунтована комплексна модель для аналізу планування гірничих робіт й визначення раціональних параметрів охорони основних підготовчих виробок у розвантажених від гірського тиску зонах. Вибрана допоміжна модель для дослідження поведінки гірничого масиву після його переходу у позамежний напружено-деформований стан. Уточнені параметри моделі, які дають можливість врахування фізичного контакту між осідаючою покрівлею й підошвою пласта, яка здимається у процесі його відпрацювання. Здійснена калібровка й тестування моделі за результатами шахтних інструментальних спостережень необоротних зрушень масиву гірничих порід.
Практичні результати. Для моделювання розвитку очисних робіт у межах блоку 11 згідно прийнятого планувального рішення була розроблена розрахункова схема, яка дала можливість змоделювати умови повної підробки земної поверхні і, таким чином, оцінити максимально можливі прояви гірського тиску під час розвитку очисних робіт. Цель. Оценка перераспределения горного давления вокруг рабочего пласта.
Meтоды. В ходе проекта плановых горных работ использовались данные шахтных инструментальных наблюдений сдвигов вокруг подготовительных выработок с помощью контурных и глубинных реперов, мониторинга дина-мики роста давления обрушившихся пород и подработанной толще на подошву отработанного пласта и конечных разностей.
Результаты. Обоснована комплексная модель для анализа планирования горных работ и определения рациональных параметров охраны основных подготовительных выработок в разгруженных от горного давления зонах. Выбрана вспомогательная модель для исследования поведения горного массива после его перехода в запредельное напряженно-деформированное состояние. Уточнены параметры модели, которые дают возможность учета физического контакта между оседающей кровлей и подошвой пласта, которая вздувается в процессе его отработки. Осуществлены калибровка и тестирование модели по результатам шахтных инструментальных наблюдений необратимых сдвигов массива горных пород.
Практические результаты. Для моделирования развития очистных работ в пределах блока 11 согласно принятого планированного решения была разработана расчетная схема, которая позволила смоделировать условия полной подработки земной поверхности и, таким образом, оценить максимально возможные проявления горного давления во время очистных работ. Purpose. Estimation of redistribution of rock pressure around the working formation.
Methods. During the project of planning mining works the data of mine instrumental observations of shifts around preparatory workings with the help of contour and depth benchmarks, monitoring of dynamics of growth of pressure of collapsed rocks and forged stratum on the bottom of the spent coal seam and final differences were used.
Findings. A computer model has been substantiated to simulate relevant parameters of panel extraction layout and determine technology of the main entries maintenance in the stress relief zone. The model was based on the final difference scheme. Mohr-Coulomb constitutive model has been selected to simulate nonlinear behavior of surrounding rock mass. Bulk and shear modulus were used to mimic elastic behavior of the rocks. To simulate irreversible actions of the rock mass, cohesion, angle of internal friction, tension limit and angle of dilation were employed as initial data. A special sub-model was developed to account for physical process of immediate roof and floor interaction behind the moving longwall. The depth of mining was 1100 m whereas the total height of the model was 1500 m, because 400 m undermined strata was accounted for. Therefore, top boundary of the model was free, lateral sides were constrained from the normal displacements, and bottom of the model was fixed.
Practical implications. Parameters of the model were verified by comparison of the abutment zone with that recommended by regulatory documents. Dynamic of ground pressure in the gob behind the moving longwall face was matched the results of the experimental monitoring of the caved strata pressure. Elastic resilience of the undermined strata was compared with measured in situ at the depth about one kilometer. Step of the main roof weighting was examined by comparison with measured in a real coal mine. The results of such verification demonstrated that parameters of the model were calibrated properly. This model is planned to involve in the process of examination of the mining layout at the prospective block 11 at “Pokrovs’ke” coal mine, Ukraine, Donbass region.